POLITICAL IDENTITY IN SUNDANESE ETHNIC: PAGUYUBAN PASUNDAN (COMMUNITY) AND REGIONAL HEAD ELECTION CONTESTATION IN 2020 - Kurnia, Dadan; Siddha, Arlan; Munawar, Luqman (Universitas Padjadjaran, 2024)
This article describes the phenomenon of Sundanese political identity by Paguyuban Pasundan in the 2020 regional head elections in various regions such as Medan City, Malawi Regency, Riau Islands Province, and Jembrana Regency, where ethnic similarities and similar interests are the two factors behind the support of Pasundan Association. in supporting one of the candidate pairs in the regional head election in that area. This article uses the theory of political identity. The research method uses qualitative descriptive analysis. The data collection method was used through a study of related literature to explore and describe how political identity is used as a basis for supporting candidate pairs. Researchers use at least two different sources or methods to collect similar data. Triangulation of sources used in this research was carried out by confirming articles that showed support for the candidate pair as well as several statements issued by the Pasundan community regarding support for the candidate pairThe results of this paper illustrate that the Pasundan community in the regional head election contest supports one pair of candidates based on the same identity. In this case, Sundanese ethnicity and similar interests, which is the struggle of the Pasundan community to fight poverty and ignorance through the availability of employment opportunities and improving the quality of education seen from the commitment of the candidate pair to carry these aspirations in their leadership if elected in the 2020 regional head election.